A new fuzzy k-modes clustering algorithm for categorical data. (25th June 2009) - Ng, Michael K.; Jing, Liping
This correspondence describes extensions to the fuzzy k-modes algorithm for clustering categorical data. We modify a simple matching dissimilarity measure for categorical objects, which allows the use of the fuzzy k-modes paradigm to obtain a cluster with strong intra-similarity, and to efficiently cluster large categorical data sets. We derive rigorously the updating formula of the fuzzy k-modes clustering algorithm with the new dissimilarity measure, and the convergence of the algorithm under the optimisation framework. Experimental results are presented to illustrate that the effectiveness of the new fuzzy k modes algorithm is better than those of the other existing k-modes algorithms.